2020
DOI: 10.4236/ojog.2020.101007
|View full text |Cite
|
Sign up to set email alerts
|

HIV+ Status and Cervical Cancer: Cytological Aspects of Cervical Smear in Cameroon Setting

Abstract: Introduction: The early detection of precancerous lesions being very important for the preventive management of cervical cancer, we felt it was important to identify these lesions on potential backgrounds including HIV-positive (HIV+) women to suggest control strategies of cervical cancer in Cameroon. Objective: To determine the prevalence of precancerous lesions in women infected with the human immunodeficiency virus (HIV), to investigate the determinants of the HIV and cervical cancer association, and to mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…They were infected with both high-risk and low-risk HPV. HIV has already been documented as a risk factor for HPV infection and persis-tence, and for multiple HPV types, even when treated with ART [29] [30] [31]. Two studies in Burkina Faso found prevalences of 58.33% and 59.5% respectively of HPV infection in HIV-positive women [20] [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were infected with both high-risk and low-risk HPV. HIV has already been documented as a risk factor for HPV infection and persis-tence, and for multiple HPV types, even when treated with ART [29] [30] [31]. Two studies in Burkina Faso found prevalences of 58.33% and 59.5% respectively of HPV infection in HIV-positive women [20] [22].…”
Section: Discussionmentioning
confidence: 99%
“…Endocervical samples were tested for HPV genotypes by Polymerase Chain Reaction (PCR)/hybridization using the HPV Direct Flow Chip kit (Vitro Master Diagnóstica). This method, based on PCR followed by hybridization, identi-fied 36 HPV genotypes, including 18 high-risk genotypes (HR-HPV) such as HPV 16,18,26,31,33,35,39,45,51,52,53,56,58,59, 66, 68, 73 and 82, and 18 low-risk genotypes (LR-HPV), namely HPV 6,11,40,42,43,44,54,55,61,62,67,69,70,71,72,81, 84 and 89. Samples were pretreated twice with DNAse/ RNAse free solution and 30 μL of each sample was then added to the PCR mix.…”
Section: Hpv Detectionmentioning
confidence: 99%